Histopathology of fatal respiratory distress caused by Plasmodium vivax malaria. - Valecha, N; Pinto, R; Turner, G; Kumar, A; Rodrigues, S; Dubhashi, N; Rodrigues, E; Banaulikar, S; Singh, R; Dash, A; Baird, J (2009)
An otherwise healthy 20-year-old woman in Goa, India, received antibiotics after a diagnosis of upper respiratory tract infection. One week later, vivax malaria was diagnosed at a health center, but the patient developed respiratory distress and lost consciousness. She arrived at emergency department in shock, breathless, and comatose. She died within minutes. Two independent laboratories later confirmed Plasmodium vivax by microscopy (140,000/microL) and by nested and real-time polymerase chain reaction methods. Post-mortem examination showed congestion of alveolar capillaries by heavy monocytic infiltrates, along with diffuse damage to alveolar membranes consistent with acute respiratory distress syndrome. Parasites seen in lung tissue were roughly proportionate to both peripheral hyperparasitemia and those seen in other organs without lesions. In this patient, vivax malaria caused a rapidly fatal respiratory distress.